Knee Joint Menisci Are Shock Absorbers: A Biomechanical In-Vitro Study on Porcine Stifle Joints - Seitz, Andreas M.; Schwer, Jonas; de Roy, Luisa; Warnecke, Daniela; Ignatius, Anita; Dürselen, Lutz (Frontiers in Bioengineering and Biotechnology, 2022)
The aim of this biomechanical in vitro study was to answer the question whether the meniscus acts as a shock absorber in the knee joint or not. The soft tissue of fourteen porcine knee joints was removed, leaving the capsuloligamentous structures intact. The joints were mounted in 45° neutral knee flexion in a previously validated droptower setup. Six joints were exposed to an impact load of 3.54 J, and the resultant loss factor (η) was calculated. Then, the setup was modified to allow sinusoidal loading under dynamic mechanical analysis (DMA) conditions. The remaining eight knee joints were exposed to 10 frequencies ranging from 0.1 to 5 Hz at a static load of 1210 N and a superimposed sinusoidal load of 910 N (2.12 times body weight). Forces (F) and deformation (l) were continuously recorded, and the loss factor (tan δ) was calculated. For both experiments, four meniscus states (intact, medial posterior root avulsion, medial meniscectomy, and total lateral and medial meniscectomy) were investigated. During the droptower experiments, the intact state indicated a loss factor of η = 0.1. Except for the root avulsion state (−15%, p = 0.12), the loss factor decreased (p < 0.046) up to 68% for the total meniscectomy state (p = 0.028) when compared to the intact state. Sinusoidal DMA testing revealed that knees with an intact meniscus had the highest loss factors, ranging from 0.10 to 0.15. Any surgical manipulation lowered the damping ability: Medial meniscectomy resulted in a reduction of 24%, while the resection of both menisci lowered tan δ by 18% compared to the intact state. This biomechanical in vitro study indicates that the shock-absorbing ability of a knee joint is lower when meniscal tissue is resected. In other words, the meniscus contributes to the shock absorption of the knee joint not only during impact loads, but also during sinusoidal loads. The findings may have an impact on the rehabilitation of young, meniscectomized patients who want to return to sports. Consequently, such patients are exposed to critical loads on the articular cartilage, especially when performing sports with recurring impact loads transmitted through the knee joint surfaces.